Depreciation of the Ugandan Shilling: Implications for the National Economy - Ntambirweki, Barbara; Jones, Emma (STON Infosheet, 2015)
Over the course of 2014/15 fiscal year, the Ugandan shilling depreciated against the US dollar by over 20%. Uganda, like many other economies, was struggling with the falling value of its’ currency against the dollar which was attributed to the fall in export commodity prices, heavily impacted by export markets. This depreciation made mobilizing capital from international markets difficult. Given the circumstances and the depreciation of the Ugandan shilling, long-term ramifications for the economy were likely. It was against this background that the Advocates Coalition for Development and Environment (ACODE) held the 59State of the Nation (STON) Platform to bring together key stakeholders for discussions on the likely impact of the falling value of the Ugandan shilling. Titled the “Depreciation of the Ugandan Shilling: Implications for the National Economy”, three main recommendations emerged; chief among them was the need to prioritise investment in the agricultural sector. Second was the need to pursue import substitution and export promotion, and thirdly the Government of Uganda (GoU) was advised to prioritise the adoption of an updated national monetary policy that reflected current economic needs.